Automated rural electrification using conventional technologies and stand-alone photovoltaic systems - Yu, Danilo Buendia; Lucas, N.J.D.; Kanchit Malaivongs; Vilas Wuwongse; Australian Government (Bangkok : Asian Institute of Technology, 1983)
An interactive computer program, through the use of a microcomputer, has been developed to determine and evaluate the design of distribution systems for rural areas. Three alternative plans of supplying power, namely; grid electrification, diesel engine electrification and stand-alone photovoltaic systems, can be compared by using present worth analysis. The program focuses its emphasis on the reduction of losses in the distribution system as the main criterion in arriving at an optimal design for distribution systems. The results of the program enable planners to make cost comparisons among the three energy resources. Program results also highlight system changes as the input parameters are varied. The importance of the program lies in its contribution in facilitating the planning aspect of rural electrification. The use of present-worth analysis in evaluating the different alternatives signifies the recognition of the time-value of money, a vital input for the development of third world countries.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1984
Keywords: Rural electrification -- Automation